Real world evidence retrospective study to evaluate the safety and efficacy of an amniotic membrane allograft for lower extremity diabetic ulcers in a post-acute care setting (International Journal of Tissue Repair, 2025)
Aims: To evaluate the reduction of lower extremity diabetic ulcer (LEDU) wound size after amniotic membrane allograft (AmnioBurgeon (OneBiotech, LLC, USA) treatment.Methods: Single center retrospective database review for patients treated with AmnioBurgeon for LEDUs. Wound area was measured prior to each allograft application and change in wound area over each application was evaluated over progression of therapy.Results: In total, 24 patients with 28 LEDUs were treated weekly with AmnioBurgeon with average wound size of 17.4cm2. During the treatment course, 14% of the wounds completely healed with a mean time to healing of 77 days. Overall, 64% of them achieved partial closure with at least 50% area reduction within 21 days on average. By week 4, 46% of wounds achieved ≥50% reduction in their size.Conclusion: Amniotic membrane allograft is an effective treatment for LEDUs which were not successful in healing with standard of care.